Strengthening Marketing Performance Through Entrepreneurial Marketing and Absorptive Capacity: Examining Strategic Alignment Mediation and Digital Capability Moderation - Budi Setiawan; Burhan Bungin; Wirawan Endro Dwi Radianto; Siti Zahro; Rommy Pramono (FOUNDAE (Foundation of Advanced Education), 2025)
In the context of digital startups in emerging markets, achieving superior marketing performance remains a critical challenge due to rapid environmental changes, intense competition, and limitations in organizational capabilities. Prior studies have emphasized the importance of Entrepreneurial Marketing (EM) and Absorptive Capacity (AC); however, the mechanism through which these capabilities translate into performance, particularly through Strategic Alignment (SA), remains underexplored. In addition, the role of Digital Capability (DC) as a potential boundary condition in strengthening alignment outcomes is still inconclusive. This study aims to examine how EM and AC enhance Marketing Performance (MP) through SA, and whether DC moderates the relationship between SA and MP in Indonesian digital startups. Using survey data from 250 firms and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that EM and AC significantly strengthen SA, which in turn exerts a strong positive effect on MP. DC also demonstrates a significant direct effect on MP; however, its moderating role in the SA–MP relationship is not supported. These results suggest that while digital capability contributes directly to performance, it does not necessarily amplify the effectiveness of strategic alignment. This study highlights SA as the primary mechanism through which EM and AC translate into superior marketing performance, while positioning DC as an operational enabler rather than a strategic amplifier. Managerially, firms are encouraged to institutionalize alignment practices and leverage digital capability to support execution effectiveness. The study contributes by advancing an integrated alignment-based framework and by clarifying the boundary conditions of digital capability in emerging-market digital startups.